Impaired left ventricular filling dynamics in patients with angina and angiographically normal coronary arteries: effect of beta adrenergic blockade. (January 1997) - Fragasso, G.; Chierchia, S. L.; Pizzetti, G.; Rossetti, E.; Carlino, M.; Gerosa, S.; Carandente, O.; Fedele, A.; Cattaneo, N.
Abstract : OBJECTIVE: To assess exercise performance and resting left ventricular filling dynamics in patients with syndrome X (SX) in basal conditions and after 10 days treatment with oral atenolol. DESIGN AND PATIENTS: Exercise performance was studied and left ventricular filling assessed by Doppler-derived transmitral flow pattern analysis in 22 patients (16 female, mean (SD) age 53 (4) years) with angina, a positive exercise test, and angiographically smooth coronary arteries. Patients were studied after two 10 day treatment periods with either atenolol or placebo in a single-blind, randomised, crossover trial. The same protocol was followed in 10 patients with documented coronary artery disease (CAD) and in 13 controls (C). RESULTS: Unlike the controls, patients with SX and those with CAD consistently showed exercise-induced ST segment abnormalities and impaired resting left ventricular filling while on placebo. Atenolol significantly reduced episodes of angina, completely prevented exercise-induced ST segment changes in 18 SX patients, and delayed their onset in all patients with CAD: in both groups the agent significantly improved Doppler-derived indices (mean (SD)) of ventricular filling (E/A 0.97 (0.27) v 1.22 (0.32) and 0.84 (0.21) v 1.19 (0.37), respectively). CONCLUSIONS: The objective documentation of left ventricular filling abnormalities may be useful in confirming the clinical diagnosis of SX and in providing objective evidence of therapeutic benefit. The similarity of the symptoms and electrocardiographic and ventricular filling abnormalities found in patients with SX and in those with CAD suggests that ischaemia is involved in both groups.